A balancing act: mTOR integrates nutrient signals to regulate redox-dependent growth and survival through SOD1. (3rd September 2018) - Tsang, Chi Kwan; Zheng, X. F. Steven
ABSTRACT: Maintaining cellular redox is critical for growth, metabolism and survival in response to changing environments. How nutrients regulate this process is a long-standing fundamental question in cell biology. Our recent study revealed a conserved mechanism by which eukaryotes, particularly cancer cells, couple nutrient signaling to dynamically regulate redox homeostasis. Abbreviations: ATP: adenosine triphosphate; Ala: alanine; C6 H12 O6 : glucose; OH − : hydroxyl radical; Glu: glutamate; mRNA: messenger RNA; mTOR: mechanistic/mammalian target of rapamycin; OXYPHOS: oxidative phosphorylation; Ser: serine; ROS: reactive oxygen species; O2 − : superoxide; SOD1: superoxide dismutase 1; Thr: threonine